Targeting of γ-tubulin complexes to microtubule organizing centers: conservation and divergence - Lin, Dennis Tien-chen; Neuner, Annett; Schiebel, Elmar (Trends in cell biology, 2015)
Organisms with closed or open mitosis have differentially evolved various gamma-tubulin complex (γ-TuC) recruiting factors to organize diverse cellular microtubule (MT) arrays, including the mitotic spindle. γ-TuC recruiting factors not only target the γ-TuC to MT nucleation sites, but also regulate MT nucleation activity by generating the template for MT nucleation or promoting the MT nucleation activity of pre-existing γ-tubulin ring complexes (γ-TuRCs). Here we outline the current understanding of MT nucleator assembly and its regulation by γ-tubulin small complex (γ-TuSC) receptors. Moreover, we discuss the emergence of γ-TuC recruiting factors through evolution with augmented complexity and diversity and propose a hypothesis to account for the evolution of these factors in cooperative spindle assembly.